2019
DOI: 10.3390/mi10020129
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis C Virus Core Protein in Serum Using Aptamer-Functionalized AFM Chips

Abstract: In the present study, we demonstrate atomic force microscopy (AFM)-based detection of hepatitis C virus (HCV) particles in serum samples using a chip with aptamer-functionalized surface (apta-based AFM chip). The target particles, containing core antigen of HCV (HCVcoreAg protein), were biospecifically captured onto the chip surface from 1 mL of test solution containing 10 µL of serum collected from a hepatitis C patient. The registration of aptamer/antigen complexes on the chip surface was performed by AFM. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 42 publications
(88 reference statements)
0
50
0
Order By: Relevance
“…Again, the hyper-conserved regions detected in our study could be novel targets for aptamer-based strategies that might work independently of clinical stage or HBV genotype. They could be also used to elaborate a new HBV detection system, as has been done with hepatitis C virus [33] and syncytial viruses [34] .…”
Section: Strategymentioning
confidence: 99%
“…Again, the hyper-conserved regions detected in our study could be novel targets for aptamer-based strategies that might work independently of clinical stage or HBV genotype. They could be also used to elaborate a new HBV detection system, as has been done with hepatitis C virus [33] and syncytial viruses [34] .…”
Section: Strategymentioning
confidence: 99%
“…The thymine amino group and ten nucleotides were included into the nucleotide sequences of aptamers to improve its covalent immobilization efficiency on the surfaces of the AFM-chip, and to level up steric hindrances in interaction with target protein molecules [3].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Four zones with immobilized aptamers (А12, А14, А15 and А16) were formed on the surfaces of working and control AFM-chips. Activation of the AFM-chip surfaces and immobilization of aptamers were carried out in accordance with the method detailed in article [3]. Arrangement of zones on the AFM-chip surfaces is presented in Supplementary Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, AFMs measure the interactions between particles, thus allowing the nanoscale study of the surfaces for different materials [2][3][4]. In fact, a wide variety of applications in the analysis of pharmaceutical products, the study of the properties of fluids and fluids in cellular detection, and studies on medicines, among others, can be found in [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%